2015
DOI: 10.1152/jn.00336.2015
|View full text |Cite
|
Sign up to set email alerts
|

Robotic therapy for chronic stroke: general recovery of impairment or improved task-specific skill?

Abstract: There is a great need to develop new approaches for rehabilitation of the upper limb after stroke. Robotic therapy is a promising form of neurorehabilitation that can be delivered in higher doses than conventional therapy. Here we sought to determine whether the reported effects of robotic therapy, which have been based on clinical measures of impairment and function, are accompanied by improved motor control. Patients with chronic hemiparesis were trained for 3 wk, 3 days a week, with titrated assistive robot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 49 publications
2
74
0
1
Order By: Relevance
“…34 Furthermore, we have recently shown that our global kinematic measure can detect changes after robotic therapy in chronic stroke that were undetectable with either FMA-UE or ARAT. 22 Thus continuous 2-D kinematic data are in fact more sensitive to small differences in motor behavior than standard clinical measures. 22,33 Moreover, it is also highly unlikely that the AMD 2 improved in parallel with the clinical measures but went undetected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…34 Furthermore, we have recently shown that our global kinematic measure can detect changes after robotic therapy in chronic stroke that were undetectable with either FMA-UE or ARAT. 22 Thus continuous 2-D kinematic data are in fact more sensitive to small differences in motor behavior than standard clinical measures. 22,33 Moreover, it is also highly unlikely that the AMD 2 improved in parallel with the clinical measures but went undetected.…”
Section: Discussionmentioning
confidence: 99%
“…22 Thus continuous 2-D kinematic data are in fact more sensitive to small differences in motor behavior than standard clinical measures. 22,33 Moreover, it is also highly unlikely that the AMD 2 improved in parallel with the clinical measures but went undetected. Analyses indicate >99% power to detect a change in AMD 2 of the same percent magnitude as was seen for the clinical measures beyond week 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In severely affected patients, performance-dependent, neuromuscular electrical stimulation of individual upper limb muscles integrated in the exoskeleton may increase the range of motion even further (Grimm and Gharabaghi, 2016; Grimm et al, 2016b). These approaches focus on the improvement of motor control, which is defined as the ability to make accurate and precise goal-directed movements without reducing movement speed (Reis et al, 2009; Shmuelof et al, 2012), or using compensatory movements (Kitago et al, 2013, 2015). Functional gains in hemiparetic patients, however, are often achieved by movements that aim to compensate the diminished range of motion of the affected limb (Cirstea and Levin, 2000; Grimm et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%